The Bible and Music - McGrath, James F. (Open textbook library., 2023)
The Bible and Music by Dr. James F. McGrath provides an introduction and overview of the various ways that music and the Bible have been and continue to be connected. Part 1 focuses on history, presenting what we know about how music in the Ancient Near East sounded, how markings in the Masoretic Text of the Hebrew Bible have been interpreted as musical symbols, how chanting of biblical texts has featured liturgically in synagogues and churches, the impact of the Protestant Reformation, and musical developments in North America as enslaved Africans encountered biblical texts and stories. Part 2 focuses on specific texts in Jewish and Christian scripture and looks at how they have been interpreted through the process of setting them to music, including the soundtracks of cinematic depictions of biblical narrative and allusions to the Bible in popular music. Part 3 focuses on composers from the Middle Ages all the way down to the present day. Throughout the book, musical examples are not merely mentioned but embedded so that reading and listening may be seamlessly combined. The book does not presume prior knowledge of either music or the Bible, and additional links within the text provide definitions and further explanations for those who need or desire them.